Public Affairs and Administration 2015
DOI: 10.4018/978-1-4666-8358-7.ch100
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Intention towards E-Government in Malaysia

Abstract: This study examines an amplified unified theory of acceptance and use of technology (UTAUT) in the context of eGovernment to get a better understanding of users' behaviour towards eGovernment. Two hundred and six respondents (206) participated in the study and the data was analysed using structural equation modelling (SEM). The study revealed that Performance Expectancy, Risk Taking Propensity, Attitude towards Computer and Web Trust dimensions are essential precursor of behavioural intention of Malaysians tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…It can be concluded that the tax authorities at KPP Madya Jakarta Selatan found that TKB was useful, was able to speed up work and was effective for completing work. In the research by Taiwo & Downe, the relationship between Performance Expectancy and Behavioural Intention was stronger and more significant than the relationships of other constructs [10]. This result also supports the research by Venkatesh The second hypothesis stating that Effort Expectancy has an effect on Behavioural Intention was accepted with a t-statistic of 2.986.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It can be concluded that the tax authorities at KPP Madya Jakarta Selatan found that TKB was useful, was able to speed up work and was effective for completing work. In the research by Taiwo & Downe, the relationship between Performance Expectancy and Behavioural Intention was stronger and more significant than the relationships of other constructs [10]. This result also supports the research by Venkatesh The second hypothesis stating that Effort Expectancy has an effect on Behavioural Intention was accepted with a t-statistic of 2.986.…”
Section: Discussionsupporting
confidence: 80%
“…In this research, the relationship between behavioral intention and use behaviour was reliable, with facilitating condition having an effect on use behaviour as found in the research by Taiwo & Downe (2013). It was found that the direct relationship was stronger than the indirect relationship.…”
Section: Discussionsupporting
confidence: 72%
“…The Unified Theory of Acceptance and Use of Technology (UTAUT) model is an integrated model developed by Venkatesh based on a cognitive, social theory with a combination of eight leading research models regarding information technology acceptance [9]. The UTAUT model has four fundamental constructs: Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions, which influence behavioral intentions to use technology [5].…”
Section: Unified Theory Of Acceptance and Use Of Technology (Utaut)mentioning
confidence: 99%